Savages - Wells, Caleb (Auckland University of Technology, 2020)
A discussion and comparison of a selection of films with regards to context, culture, and genre to provide insight into 'SAVAGES', a new screenplay discussed in the second half. SAVAGES is a story of a wealthy family torn apart by their father’s cruelty and mistreatment. They come together in an attempt to preserve their wealth but end up finding an unexpected connection with each other. The texts examined and compared in detail here will be The Killing of a Sacred Deer, written by Yorgos Lanthimos and Efthymis Filippou; Happy End, written by Michael Haneke; Catfight, written by Onur Turkel; The Square, written by Ruben Östlund; and television dramedy Succession, created by Jesse Armstrong.
Keywords: Black comedy; Satire; Wealth; Power; Corruption